ANALISIS PENGARUH PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING PADA MATA PELAJARAN GAMBAR TEKNIK - Fildzah Ghassani Athaya (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
Vocational education currently requires students to be more active, creative, independent, explore their knowledge and abilities in carrying out learning activities. Therefore, teachers are required to choose the right learning model so that students are more motivated when carrying out learning, one of which is the Technical Drawing subject which is a basic subject that must be mastered by vocational students. The Project Based Learning learning model is an educational approach that emphasizes learning through direct involvement of students in projects that are real and relevant to everyday life. This study aims to analyze the effect of the Project Based Learning model on learning activities and student learning outcomes. The research method used is literature review, the author analyzes several journals, articles, or reading sources that are relevant to the related title. Through this analysis, it was found that Project Based Learning has a positive influence on student activeness during learning activities and increased student learning outcomes. This article contains an analysis of the effect of applying Project Based Learning in Engineering Drawing courses to provide insight for educators in determining effective learning models.